Effect of the competency-based Helping Mothers Survive Bleeding after Birth (HMS BAB) training on maternal morbidity: a cluster-randomised trial in 20 districts in Tanzania. Issue 2 (7th March 2019) - Alwy Al-beity, Fadhlun; Pembe, Andrea; Hirose, Atsumi; Morris, Jessica; Leshabari, Sebalda; Marrone, Gaetano; Hanson, Claudia
Abstract : Background: Training health providers is an important strategy to improve health. We conducted a cluster-randomised two-arm trial in Tanzania to assess the effect of a 1-day competency-based training 'Helping Mothers Survive Bleeding after Birth (HMS BAB)' followed by eight weekly drills on postpartum haemorrhage (PPH)-related morbidity and mortality. Methods: Twenty districts in four purposefully selected regions in Tanzania included 61 facilities. The districts were randomly allocated using matched pairs to ensure similarity in terms of district health services in intervention and comparison districts. In the 10 intervention districts 331 health providers received the HMS BAB training. The other half continued with standard practices. We used the WHO's near miss tool to collect information on severe morbidity (near misses) of all women admitted to study facilities. We performed interrupted time series analysis to estimate differences in the change of near miss per delivery rate and case fatality rates. We also assessed implementation of evidence-based preventive and basic management practices for PPH as secondary outcomes. Results: We included 120 533 facility deliveries, 6503 near misses and 202 maternal deaths in study districts during study period (November 2014 to January 2017). A significant reduction of PPH near misses was found among women who suffered PPH in the intervention district compared with comparison districts (difference-in-differences of slopes −5.3, 95% CI −7.8 to −2.7, p<0.001) from a baseline PPH-related near miss rate of 71% (95% CI 60% to 80%). There was a significant decrease in the long-term PPH near miss case fatality (difference-in-differences of slopes −4 to 0) (95% CI −6.5 to −1.5, p<0.01) in intervention compared with the comparison districts. The intervention had a positive effect on the proportion of PPH cases treated with intravenous oxytocin (difference-in-differences of slopes 5.2, 95% CI 1.4 to 8.9) (p <0.01). Conclusion: The positive effect of the training intervention on PPH morbidity and case fatality suggests that the training addresses important deficits in knowledge and skills. Trial registration number: PACTR201604001582128.